2020
DOI: 10.1002/nbm.4412
|View full text |Cite
|
Sign up to set email alerts
|

Integrated quantitative susceptibility and R2* mapping for evaluation of liver fibrosis: An ex vivo feasibility study

Abstract: To develop a method for noninvasive evaluation of liver fibrosis, we investigated the differential sensitivities of quantitative susceptibility mapping (QSM) and R 2 * mapping using corrections for the effects of liver iron. Liver fibrosis is characterized by excessive accumulation of collagen and other extracellular matrix proteins. While collagen increases R 2 * relaxation, measures of R 2 * for fibrosis are confounded by liver iron, which may be present in the liver over a wide range of concentrations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
1
8
1
Order By: Relevance
“…Jafari et al showed that R2* in human fibrotic liver explant samples significantly increased compared with that in nonfibrotic samples, while the difference in susceptibility was nonsignificant. 27 In contrast, our study showed significant increase in susceptibility. Our study used WF separation method for QSM reconstruction, while the ex vivo study used simultaneous phase unwrapping and removal of chemical shift (SPURS).…”
Section: Qsm Versus R2* In Liver Fibrosiscontrasting
confidence: 93%
See 1 more Smart Citation
“…Jafari et al showed that R2* in human fibrotic liver explant samples significantly increased compared with that in nonfibrotic samples, while the difference in susceptibility was nonsignificant. 27 In contrast, our study showed significant increase in susceptibility. Our study used WF separation method for QSM reconstruction, while the ex vivo study used simultaneous phase unwrapping and removal of chemical shift (SPURS).…”
Section: Qsm Versus R2* In Liver Fibrosiscontrasting
confidence: 93%
“…26 To the best of our knowledge, few studies have compared QSM analysis and the status of liver fibrosis. An ex vivo feasibility study exists, 27 but there is no in vivo study.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Over the past decade, QSM has proven to be a promising tool for various brain applications, including the assessment of iron deposits in deep gray matter, 2,5 demyelination in white matter, 2 differentiation of blood products and calcifications, 4,6 estimation of vessel oxygenation and geometry, 7,8 and its use as a potential biomarker of several neurodegenerative diseases. 2,4,5,[9][10][11] Recently, QSM has gained interest for applications outside the brain, for example, as a biomarker for hepatic iron overload 12,13 and fibrosis, 14,15 and chronic kidney disease. 16 Unlike in the brain, the application of QSM in the abdomen involves a series of additional challenges and restrictions 12,14,17 : reduced acquisition times and resolution, undesired signal contributions from fat and gases, rapid signal decay in tissues with high iron concentrations, and different kinds of motion.…”
Section: Introductionmentioning
confidence: 99%
“…24 Regardless of the chosen approach, abdominal QSM reconstructions tend to be over-regularized to minimize artifacts, resulting in maps with low details that only provide significant information for severe conditions or diseases. 12,14,16,25 Furthermore, the absence of a reliable ground-truth hinders the development of a more precise and effective dipole inversion approach for abdominal applications that could effectively manage such specific limitations. On the one hand, in vivo abdominal ground-truth data could not be developed using methods like COSMOS 26 or STI, 27 given the unfeasibility to acquire multiple orientation images in the abdomen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation